If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -5s = -11 Solving 2 + -5s = -11 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5s = -11 + -2 Combine like terms: 2 + -2 = 0 0 + -5s = -11 + -2 -5s = -11 + -2 Combine like terms: -11 + -2 = -13 -5s = -13 Divide each side by '-5'. s = 2.6 Simplifying s = 2.6
| 71-3x=7x-21 | | 2358=287+5x | | (2x-1)(3x+4)=2 | | 59-7x=2x+18 | | 3y+12=3y | | 9x-2(4x+5)=32 | | x+x+2+x+4=147 | | -0.6=-3 | | =3a+7b+4+7a | | -6=x-(3-4x) | | 3x-8=-23 | | 3x+23=11x-49 | | -6a+11=-22 | | 8h-9=8h | | 3(-14+2)=13 | | 4x-30=2x+20 | | =8x+y+4x+2y | | 8s+6=54 | | -5,3/4=-2,1/2(m) | | -4.8f+9=-5 | | 3x+5=2x-2 | | 3p-200=200-2p | | x+50x=220 | | 4(2n+9)+15n=30n-6 | | x-143+512=745 | | (x+6)(x-9)=-14 | | 4x=3x-1+5+2x | | =x+3y+12+5y | | 2/3-9=6-2/3 | | -2p+(8p-6)=-18 | | 5(4Z-1)-3(2+7)=14(Z+1) | | =2x+9y+6x |